The Effects Of Organizational Behaviour On Employee Job Satisfaction Affecting Information Technology Investments In Global Banks - Terry, Leong Kian Seong (2014)
This study examines the effects of 2 strategic areas of organization behaviour, namely organizational culture and organizational politics on employee job satisfaction. It assesses how these 2 areas of organizational behaviour could affect the outcome of the employee job satisfaction in order to maximize profits and business growth through IT investments for global banks. To attain its objectives, this study utilized quantitative approach by distributing survey questionnaire to the individuals who have at least 2 years and above working experience with global banks having presence in Malaysia and Singapore. A total of 76 usable responses were received. This study revealed a focus of Employee Job Satisfaction, 2 categories of Organizational Culture (Motivators & Hygiene Factors) and 3 categories of Perception of Organizational Politics (General Political Behaviour, Going Along to Get Ahead & Pay and Promotion). The results of the survey indicate that the presence of both Organizational Culture factors, Motivators & Hygiene Factors, have positive effect on Employee Job Satisfaction. On the contrary, there is a negative correlation of Perception of Organizational Politics with Employee Job Satisfaction.